The use of a pro forma to improve quality in clerking vascular surgery patients. Issue 1 (3rd March 2016) - Kentley, Jonathan; Fox, Amy; Taylor, Sophia; hassan, yahya; Filipek, Alicja
Abstract: At our institution, a large tertiary referral centre for vascular surgery, patients are often admitted directly to the ward and clerked by foundation year one (FY1) doctors. We found that these clerkings frequently fell short of national record keeping standards, potentially leading to an increased risk for patients during their hospital stay. In addition, we found that junior doctors did not feel confident in clerking vascular surgery patients. A literature review found that high quality clerkings were strongly linked to improved patient safety, and that the use of a pro forma was one method to improve compliance with documentation guidelines. We devised a clerking pro forma based on national guidelines and introduced it to the department. We found that the use of a pro forma significantly improved documentation standards across a number of domains, including patient demographics, presenting complaint, and family and social histories (p <0.05). Examinations were significantly more comprehensive, with cardiac and vascular examination as well as peripheral pulses documented (p <0.05). In conclusion, we found that using a pro forma helped to aid junior doctors in clerking new patients, and significantly improved the quality of their history and examinations. This leads to a potential positive impact on patient safety during their inpatient stay, and should be rolled out more widely across the hospital.